RASIONALITAS PETANI DALAM MERESPONS PERUBAHAN KELEMBAGAAN PENGUASAAN LAHAN DAN SISTEM PANEN PADA USAHATANI PADI - M.Saleh S. Ali; Awalauddin Yunus; Darmawan Salman (Hasanuddin University, 2018)
AbstractBasically human are rational beings that always consider the principle of efficiency and effectiveness in performing every action. They will always tend to maximize their rationality. This study aims to analyze the rationality of farmers in responding to institutional changes in rice farming, especially in the procurement of agricultural land and harvest. The paradigm used is postpositives, with a single case study focusing on farmers ' rational and agricultural institutional changes in response to the institutional change. This research conducted in Bonto Marannu Village, Lau District, Maros Regency, South Sulawesi. The data were analyzed descriptively qualitatively, by comparing between the time of institutional change before and after the use of superior seeds of rice farmers. Informants were from farmers ' households, and related actors determined by snowballs/a snowball/the snowball sampling technique. The results showed changes in the rationality of farmers associated with changes in agricultural institutions. If the farmers in the process of production, formerly practice mutual assistance through barter transactions, have transformed into transactions in the form of wages, and differentiation in the community of paddy farmers into agricultural labor, professional labor, farm managers, and entrepreneur farmers as owners capital, as a transition of feudalism to capitalism. This study concludes that farmers have responded to institutional and land-harvesting changes in rational instrumental through innovative and technological developments and has deregulated subsistence roots into commercial-based market economies. Keywords: farmers; rationality; institutional change; rice farming